ANALYSIS OF GOOD CORPORATE GOVERNANCE, DEBT COSTS, AND INVENTORY INTENSITY AGAINST TAX MANAGEMENT - Ester Hanna Gunawan; Faza Wahyu Anggrainy; Sultan Maulana Hakim (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study aims to analyze the influence of good corporate governance, debt costs, and inventory intensity on tax management in consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) during the 2018-2022 period. The method used is a quantitative method with secondary data from the financial statements of consumer non-cyclicals sector companies listed on the IDX in the period. The sample selection method used was the purposive sampling method by producing 27 companies for five years with a total of 135 observations. Data were analyzed using E-Views software 13. The results of the study show that: (1) Good corporate governance, debt costs, and inventory intensity simultaneously have a significant effect on tax management; (2) Good corporate governance does not have a significant effect on tax management; (3) Debt costs do not have a significant effect on tax management; (4) Inventory intensity has a positive and significant effect on tax management.